Simultaneous spectrophotometric determination of drugs lacking peak maxima in their zero-order profiles by graphical or statistical representation of data - Magdy, Ragaa; Hemdan, Ahmed; Fares, Nermine Victor; Farouk, Maha (European Journal of Chemistry, 2018)
Trandolapril has no sharp peak in its zero-order spectrum, therefore it is difficult to be measured by direct spectrophotometry. In this study, direct univariate spectrophotometric methods were developed and validated for determination of Trandolapril and Verapamil combination in pure and tablet dosage forms. The first method for measuring both Trandolapril and Verapamil is Absorbance Subtraction (AS), this method depends on the presence of iso-absorptive point in the zero-order curve at 217 nm. It has the advantage of measuring the concentration of both Trandolapril and Verapamil from unified regression equation at the iso-absorptive point. The second, third and fourth methods were applied on the first order spectra of the studied drugs. Second method is Derivative Subtraction (DS) for Trandolapril and Derivative subtraction followed by spectrum subtraction (DS-SS) for Verapamil. The third and fourth methods are constant value and concentration value methods. In the concentration value method, the concentration of the drugs is determined from the graphical representation without the use of regression equations. All the developed methods were validated as per International Conference on Harmonization guidelines and the results proved that the developed methods are simple, accurate, and selective. Moreover, a statistical comparison between the developed methods and a reference method was done. Also, One-way ANOVA statistical test was done between all the proposed spectrophoto-metric methods and results showed no significant differences.